Evapotranspiration loss of water from rice and wheat plants grown in sand and sandy soil in bottom closed earthen pots under gravity irrigation system - Rahman, Md Khalilur (Bangladesh Journal of Scientific Research, 2016)
Abstract not available Bangladesh J. Sci. Res. 28(2): 181-184, Dec-2015